2018
DOI: 10.1002/advs.201800529
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inflammatory Cytokines for Spinal Cord Injury Repair Through Local Delivery of Therapeutic Agents

Abstract: The balance of inflammation is critical to the repair of spinal cord injury (SCI), which is one of the most devastating traumas in human beings. Inflammatory cytokines, the direct mediators of local inflammation, have differential influences on the repair of the injured spinal cord. Some inflammatory cytokines are demonstrated beneficial to spinal cord repair in SCI models, while some detrimental. Various animal researches have revealed that local delivery of therapeutic agents efficiently regulates inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 253 publications
(348 reference statements)
0
52
0
Order By: Relevance
“…In addition, inflammatory cells also release excess reactive oxygen species and reactive nitrogen species [66,67], which causes DNA oxidative damage, proteins oxidation and lipid peroxidation [68]. Necrosis and apoptosis of neurons and glial cells are further induced by this process [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inflammatory cells also release excess reactive oxygen species and reactive nitrogen species [66,67], which causes DNA oxidative damage, proteins oxidation and lipid peroxidation [68]. Necrosis and apoptosis of neurons and glial cells are further induced by this process [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…(d) AS‐IV ameliorates secondary damage in the injured spinal cord and promotes locomotor function recovery after SCI in rats. Neuronal apoptosis and neuroinflammation are extremely important in the pathological process of secondary injury after SCI . Numerous studies have targeted these two pathological processes for SCI therapy; however, barely any therapies could target both these two pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that (a) AS-IV promotes autophagy and inhibits neuronal apoptosis after SCI. 8,[23][24][25] Numerous studies have targeted these two pathological processes for SCI therapy; however, barely any therapies could target both these two pathological processes. In our study, we found that AS-IV possesses 'one stone two birds' potential, which not only inhibits neuronal apoptosis but also suppresses neuroinflammation through inhibiting the mTORC1 signalling pathway (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response to primary structural changes in the spinal cord is accompanied by the release of a large number of regulatory peptides, including proinflammatory ones, and cytokines [ 20 , 21 ]. Cytokines are synthesized by activated macro- and microglia, damaged vascular endothelium, as well as the immune system cells mobilized from the systemic circulation to the injury site and the adjacent areas, due to changes in the BBB permeability [ 22 ].…”
Section: Immune and Cytokine Responses During The Acute Post-traummentioning
confidence: 99%